1994
DOI: 10.1111/j.1442-200x.1994.tb03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant lavage in a rabbit model of meconium aspiration syndrome

Abstract: Meconium aspiration syndrome (MAS) is a frequent cause of respiratory distress in neonates. Recent reports have suggested that surfactant dysfunction contributes to the pathophysiology of MAS and surfactant therapy improves oxygenation of infants with MAS. We evaluated the effect of bronchial lavage with surfactant solution in a rabbit model of meconium aspiration. All animals were given 5 mL/kg of a 20% slurry of human meconium into the endotracheal tube and mechanically ventilated. The animals were then divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…In prior studies, meconium was simply administered directly into the normal lung of an animal, including piglets, rats, rabbits, and monkeys [6,8,[25][26][27][30][31][32]. Using this technique, both Cochrane et al [10] and 1 Sun et al [9] suggested that the meconium was unevenly distributed in the lung, leaving certain residual lung regions that appeared well expanded and even normal, presumably because they were beyond the reach of the meconium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior studies, meconium was simply administered directly into the normal lung of an animal, including piglets, rats, rabbits, and monkeys [6,8,[25][26][27][30][31][32]. Using this technique, both Cochrane et al [10] and 1 Sun et al [9] suggested that the meconium was unevenly distributed in the lung, leaving certain residual lung regions that appeared well expanded and even normal, presumably because they were beyond the reach of the meconium.…”
Section: Discussionmentioning
confidence: 99%
“…This has been the basis for exogenous surfactant administration in this disorder. Accordingly, animal [6,[25][26][27][30][31][32]38] and human [1,12,17,18,22] studies have addressed the question of exogenous surfactant treatment in MAS. While the results in animal studies were promising, only one randomized trial of bolus exogenous surfactant has been reported in infants with MAS [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar experimental studies on the use of SLL in the treatment of MAS were conducted at different centers by Dargaville et al 9 and Ogawa and co-workers. [10][11][12] The first clinical studies on SLL were conducted by Ogawa 10 and Lam and Yeung. 13 Ogawa administered as a lavage a surfactant solution with a concentration of 12 mg of phospholipids in 1 ml of physiological salt.…”
Section: Discussionmentioning
confidence: 99%
“…13 Ogawa administered as a lavage a surfactant solution with a concentration of 12 mg of phospholipids in 1 ml of physiological salt. Earlier, Ohama et al 11 attempted to prove that a higher concentration is more effective. The volume of the solution was 5 ml per kg of body weight.…”
Section: Discussionmentioning
confidence: 99%